2014
DOI: 10.1371/journal.pone.0102096
|View full text |Cite
|
Sign up to set email alerts
|

Axl Tyrosine Kinase Protects against Tubulo-Interstitial Apoptosis and Progression of Renal Failure in a Murine Model of Chronic Kidney Disease and Hyperphosphataemia

Abstract: Chronic kidney disease (CKD) is defined as the progressive loss of renal function often involving glomerular, tubulo-interstitial and vascular pathology. CKD is associated with vascular calcification; the extent of which predicts morbidity and mortality. However, the molecular regulation of these events and the progression of chronic kidney disease are not fully elucidated. To investigate the function of Axl receptor tyrosine kinase in CKD we performed a sub-total nephrectomy and fed high phosphate (1%) diet t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Gas6/Axl signaling regulates various cellular functions, such as survival, proliferation, adhesion, migration, blood clot stabilization, and inflammatory cytokine release [ 102 ]. Within the kidney, Axl and Gas6 are expressed in VSMCs, glomerular mesangial cells and tubular cells [ 103 ].…”
Section: Growth Arrest-specific Gene 6 (Gas6) and Axl Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…Gas6/Axl signaling regulates various cellular functions, such as survival, proliferation, adhesion, migration, blood clot stabilization, and inflammatory cytokine release [ 102 ]. Within the kidney, Axl and Gas6 are expressed in VSMCs, glomerular mesangial cells and tubular cells [ 103 ].…”
Section: Growth Arrest-specific Gene 6 (Gas6) and Axl Receptormentioning
confidence: 99%
“…The basal expression of Gas6/Axl is low in normal kidney. However, its expression can be upregulated in several murine models of CKD including: glomerulonephritis induced by Thy1.1 antibody, nephrotoxic nephritis (NS), STZ-induced DN and a podocyte ablation model of glomerular albuminuria [ 103 ]. Patients with CKD had elevated plasma Gas6 levels [ 104 ].…”
Section: Growth Arrest-specific Gene 6 (Gas6) and Axl Receptormentioning
confidence: 99%
“…To determine the role of PKCα in uremia-induced arterial medial calcification, we used the two-stage subtotal nephrectomy and high phosphate diet model [24][25][26] . Female mice were used as our pilot studies showed that they were more resistant to acute renal failure following the uni-nephrectomy in the second surgical procedure compared with males (results not shown).…”
Section: Figure 1 Generation Of Pkcαmentioning
confidence: 99%
“…Therefore, this study aimed to determine whether loss of PKCα affects uremia-induced arterial medial calcification in vivo using the murine sub-total nephrectomy and high phosphate diet model [24][25][26] . Using novel X-ray micro computed tomography (µCT) approaches, we demonstrate that uremia-induced arterial medial calcification is increased significantly in PKCα -/mice compared to wild-type controls.…”
Section: Introductionmentioning
confidence: 99%
“…GAS6/AXL is known to reduce tubulo-interstitial apoptosis in chronic kidney injury models 43 and upregulation of this axis promotes glomerular hypertrophy in diabetic mice 44 . AXL expression is primarily located in vascular endothelia and the proximal tubule 45 .…”
Section: Leptospirosismentioning
confidence: 99%